Optimalisasi Media Promosi Digital Dan Cetak Dalam Membangun Citra Po Keni Jaya Mandiri Di Kabupaten Pati - Dita Dwi Susilowati; Arni Ernawati; Annas Marzuki Sulaiman; Ahmad Akrom; Erisa Adyati Rahmasari (CITRAKARA, 2026)
This study aims to optimize digital and print promotional media to build PO's image. Keni Jaya Mandiri in Pati Regency. The main problem lies in the marketing strategy, which is still limited to social media and word of mouth, resulting in an optimal market reach. The method used is qualitative, based on interviews, observation, documentation, and literature review, with 5W+1H analysis and a Design Thinking approach. The results of the study include the design of a 1-minute 30-second commercial advertising video as the main medium to showcase service advantages cinematically, along with supporting media such as posters, X-banners, business cards, mugs, and key chains. The target audience is people aged 20–60 years in Pati Regency who serve as decision-makers. The results show that the combination of digital and print media is effective in increasing visibility, strengthening the company's image, and encouraging customer loyalty. This strategy supports broader and sustainable marketing development.